Divergent evolution of two corticotropin-releasing hormone (CRH) genes in teleost fishes - Grone, Brian P.; Maruska, Karen P. (Frontiers in Neuroscience, 2015)
Genome duplication, thought to have happened twice early in vertebrate evolution and a third time in teleost fishes, gives rise to gene paralogs that can evolve subfunctions or neofunctions via sequence and regulatory changes. To explore the evolution and functions of corticotropin-releasing hormone (CRH), we searched sequenced teleost genomes for CRH paralogs. Our phylogenetic and synteny analyses indicate that two CRH genes, crha and crhb, evolved via duplication of crh1 early in the teleost lineage. We examined the expression of crha and crhb in two teleost species from different orders: an African cichlid, Burton’s mouthbrooder, (Astatotilapia burtoni; Order Perciformes) and zebrafish (Danio rerio; Order Cypriniformes). Furthermore, we compared expression of the teleost crha and crhb genes with the crh1 gene of an outgroup to the teleost clade: the spotted gar (Lepisosteus oculatus). In situ hybridization for crha and crhb mRNA in brains and eyes revealed distinct expression patterns for crha in different teleost species. In the cichlid, crha mRNA was found in the retina but not in the brain. In zebrafish, however, crha mRNA was not found in the retina, but was detected in the brain, restricted to the ventral hypothalamus. Spotted gar crh1 was found in the retina as well as the brain, suggesting that the ancestor of teleost fishes likely had a crh1 gene expressed in both retina and brain. Thus, genome duplication may have freed crha from constraints, allowing it to evolve distinct sequences, expression patterns, and likely unique functions in different lineages.